2020
DOI: 10.1113/jp279455
|View full text |Cite|
|
Sign up to set email alerts
|

Nitrate attenuates high fat diet‐induced glucose intolerance in association with reduced epididymal adipose tissue inflammation and mitochondrial reactive oxygen species emission

Abstract: Key points Dietary nitrate is a prominent therapeutic strategy to mitigate some metabolic deleterious effects related to obesity. Mitochondrial dysfunction is causally linked to adipose tissue inflammation and insulin resistance. Whole‐body glucose tolerance is prevented by nitrate independent of body weight and energy expenditure. Dietary nitrate reduces epididymal adipose tissue inflammation and mitochondrial reactive oxygen species emission while preserving insulin signalling. Metabolic beneficial effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 51 publications
3
30
0
Order By: Relevance
“…Consistent with previous reports, Brunetta et al . (2020) found that HFD feeding impaired whole‐body glucose tolerance, which was attenuated by dietary nitrate supplementation (Kina‐Tanada et al . 2017).…”
Section: High Fat Diet Drives Adipose Tissue Dysfunction and Risk Facmentioning
confidence: 99%
See 4 more Smart Citations
“…Consistent with previous reports, Brunetta et al . (2020) found that HFD feeding impaired whole‐body glucose tolerance, which was attenuated by dietary nitrate supplementation (Kina‐Tanada et al . 2017).…”
Section: High Fat Diet Drives Adipose Tissue Dysfunction and Risk Facmentioning
confidence: 99%
“…Additional trials are needed to determine if the compelling preclinical data presented by Brunetta et al . (2020) can be translated to obese adults.…”
Section: High Fat Diet Drives Adipose Tissue Dysfunction and Risk Facmentioning
confidence: 99%
See 3 more Smart Citations